1998
DOI: 10.1287/inte.28.4.94
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of a Performance Measurement Project at RTZ

Abstract: In 1994, RTZ Corporation plc, the world's largest mining company, tried to reconcile (a) the desire of central management to compare performance across mine sites with (b) the desire of local management to judge performance in their own terms. The company began a project to establish a method of measuring open-pit productive capacity, to spread best practice, and to motivate higher performance. Initially we saw the solution as a simple model of equipment availability using hard OR derived using a participative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Rosenhead (1989) views soft OR and hard OR as complementary to each other when he notes that they are two distinct consulting activities, problem structuring and problem solving, respectively. Pauley and Ormerod (1998) explain how to blend the two. Rosenhead (1989) covers the different approaches considered parts of soft OR.…”
Section: Expertise In Problem Structuringmentioning
confidence: 99%
“…Rosenhead (1989) views soft OR and hard OR as complementary to each other when he notes that they are two distinct consulting activities, problem structuring and problem solving, respectively. Pauley and Ormerod (1998) explain how to blend the two. Rosenhead (1989) covers the different approaches considered parts of soft OR.…”
Section: Expertise In Problem Structuringmentioning
confidence: 99%
“…Colombia (Henao and Franco, 2016); and South Africa (Pauley and Ormerod, 1998;Petkov et al, 2008;Siriram, 2012). Research has demonstrated the many sectors that multimethodologies have been applied to.…”
Section: Multimethodology In Actionmentioning
confidence: 99%
“…Several authors also highlight the importance of data integration or data utilisation and how it may be undervalued in mining. 3,11,16 The first, third, and fourth developmental phases tend to deal with managerial issues and technologies. The focus of this paper relates to the key issues that confront the development of a data infrastructure appropriate for tactical mine management.…”
Section: Five Phase Tmms Methodologymentioning
confidence: 99%